2013
DOI: 10.1007/s10926-013-9418-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary Healthcare Professionals’ Experiences of the Sick Leave Process: A Focus Group Study in Sweden

Abstract: Purpose: The aim of this study was to explore primary healthcare (PHC) professionals' experiences of the sick leave process.Methods: This is an explorative study using data from four semi-structured focus group discussions with a purposeful sample of PHC professionals in Östergötland County, Sweden.Content analysis with an inductive approach was used in the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…It is conceivable that the diagnostic process may differ between countries due to the different healthcare and social insurance systems. It is also possible that the diagnostic procedure lacks precision, as physicians find it more difficult to determine symptombased diagnoses [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the diagnostic process may differ between countries due to the different healthcare and social insurance systems. It is also possible that the diagnostic procedure lacks precision, as physicians find it more difficult to determine symptombased diagnoses [47].…”
Section: Discussionmentioning
confidence: 99%
“…GPs often found the decision about issuing a sickness certificate difficult, especially if the patients describe symptoms without clinical findings [21, 24]. Likewise, GPs stated that they had poor knowledge of the workplace environment and the labor market [23, 25], and they reported that they barely talked to patients about their work situation [26, 27]. Today, GPs have no established practice for early identification of patients at risk for sick leave caused by adverse psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
“…Many qualitative studies have showed that issuing sick leave is a burden on general practitioners daily work and carries many challenges with each encounter. 3,18 The high patient demand of sickness certification might affect the quality of clinical consultations and overall performance of clinical system.…”
Section: Discussionmentioning
confidence: 99%